A global meta-analysis of livestock grazing impacts on soil properties - Lai, Liming; Kumar, Sandeep (PLOS ONE, 2020)
Grazing effects on soil properties under different soil and environmental conditions across the globe are often controversial. Therefore, it is essential to evaluate the overall magnitude and direction of the grazing effects on soils. This global meta-analysis was conducted using the mixed model method to address the overall effects of grazing intensities (heavy, moderate, and light) on 15 soil properties based on 287 papers published globally from 2007 to 2019. Our findings showed that heavy grazing significantly increased the soil BD (11.3% relative un-grazing) and PR (52.5%) and reduced SOC (-10.8%), WC (-10.8%), NO3- (-23.5%), and MBC (-27.9%) at 0–10 cm depth, and reduced SOC (-22.5%) and TN (-19.9%) at 10–30 cm depth. Moderate grazing significantly increased the BD (7.5%), PR (46.0%), and P (18.9%) (0–10 cm), and increased pH (4.1%) and decreased SOC (-16.4%), TN (-10.6%), and P (-23.9%) (10–30 cm). Light grazing significantly increased the SOC (10.8%) and NH4+ (28.7%) (0–10 cm). Heavy grazing showed much higher mean probability (0.70) leading to overgrazing than the moderate (0.14) and light (0.10) grazing. These findings indicate that, globally, compared to un-grazing, heavy grazing significantly increased soil compaction and reduced SOC, NO3-, and soil moisture. Moderate grazing significantly increased soil compaction and alkalinity and reduced SOC and TN. Light grazing significantly increased SOC and NH4+. Cattle grazing impacts on soil compaction, SOC, TN, and available K were higher than sheep grazing, but lower for PR. Climate significantly impacted grazing effects on SOM, TN, available P, NH4+, EC, CEC, and PR. Heavy grazing can be more detrimental to soil quality based on BD, SOC, TN, C: N, WC, and K than moderate and light grazing. However, global grazing intensities did not significantly impact most of the 15 soil properties, and the grazing effects on them had insignificant changes over the years.